LEKSIKON EKOBUDAYA DALAM TRADISI TURUN TANAH PADA MASYARAKAT MELAYU SAMBAS - Tia Feblia; Ahadi Sulissusiawan; Agus Syahrani (Universitas Tanjungpura, 2021)
This study aims to describe the eco-cultural lexicons in the ‘Turun Tanah’ Tradition in the Sambas Malay community at Semperiuk A village. The method used in this study was descriptive in the form of qualitative research. The data source was from the informants from the Semperiuk A village who understand the tradition. The collected data was in the form of eco-cultural lexicons related to the classification of eco-cultural lexicons, word meaning, community understanding, wisdom values, and the function. The data collection techniques used were questionnaires, observation, and interviews. Based on the results, there are five activities in the ‘Turun Tanah’ tradition. These activities are divided into two groups: tools and materials used, and the food served. From the two groups, there are 39 lexicons, each with 17 lexicons. The meaning of eco-cultural lexicons contains lexical meanings, and the community understanding of eco-cultural lexicons is categorized as still known. The wisdom value in the five activities in ‘Turun Tanah’ traditions is besaprah (eating together), bemasak (cooking), ziarah (pilgrimage), tahlel (dhikr), and ngaji (reciting the Quran). In terms of its function, the lexicons work as a complement to dishes, symbols or images, and tools for cooking purposes. Keywords: Eco-cultural, Sambas Malay, Turun Tanah